ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2011-2015 - Rizqi Alfi Handayani, 14.05.52.0104; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2018)
This study examines the Factor Analysis that affect the Company Value. This research is conducted at Indonesia Stock Exchange by using mining company which have go public.Â The population in this study is all companies listed on the Indonesia Stock Exchange in 2011 to 2015. The sample used in this study are all mining companies.Â The results of this study indicate that liquidity has a positive effect is not significant, firm growth has a significant positive effect, firm size, debt policy and institutional ownership have no significant effect on firm value. Keywords: liquidity, company growth, firm size, debt policy and institutional ownership and corporate value.